Influences of Total Quality Management on Innovation Performance and Organizational Learning - Al Maamari A.S.S.; Isa A.B.M. (World Scientific and Engineering Academy and Society, 2024)
Throughout history, businesses have struggled to maintain and improve organisational performance in an effort to maintain a competitive advantage. The important elements of the quality management system must be confirmed by the senior management of the organization to increase and enhance performance. The purpose of this article is to identify the most significant quality factors as predictors of innovation performance in Oman. It focuses on top management support, employee involvement, customer focus, and continuous improvement. The study's empirical data, which came from a self-administered survey, served as its foundation. The Ministry of Public Authority for Special Economic Zones and Free Zones and the Ministry of Commerce, Industry, and Investment Promotion, which identify 260 enterprises, provided the information. Data gathering involved the use of convenient sampling. Moreover, SMART-PLS was used to analyse the data. The study found that top management, consumer support, and employee involvement have a favourable impact on organisational learning and innovation performance. The study did discover a negligible effect of continuous quality improvement on organisational learning and innovation performance. The study suggests that future research be conducted to investigate the factors that can have a positive impact on organisational performance and innovation through continuous quality improvement. 2023, World Scientific and Engineering Academy and Society. All rights reserved.